Problem of the Week

Problem 20 Solution


Congratulations to Yat Sum Ho from Cambourne Village College for successfully solving this problem!

i)
Assume that \sqrt{3+2\sqrt{2}} can be written in the form of \sqrt{a^2+2ab+b^2}, which will allow us to write it as \sqrt{(a+b)^2} = a+b.

If this is true, a^2 + b^2 = 3 and 2ab = 2\sqrt{2} \implies ab=\sqrt{2}

Having a = 1 and b = \sqrt{2} satisfy these two equations, which yields

\sqrt{3+2\sqrt{2}} = 1+\sqrt{2}

ii) \sqrt{4\sqrt{2} + 4\sqrt{3-2\sqrt{2}}}

To begin with, we can factor out a 2 from this square root, giving us 2\sqrt{\sqrt{2} + \sqrt{3-2\sqrt{2}}}
The inner square root looks quite similar to part (i), so it is reasonable to try approach it with the same strategy.

\sqrt{3-2\sqrt{2}} = \sqrt{a^2+2ab+b^2}.

Having a = 1 and b = -\sqrt{2} satisfies a^2 + b^2 = 3 and ab=-\sqrt{2}

This means that our original expression = 2\sqrt{\sqrt{2} + 1-\sqrt{2}} = 2

Site Search